Experience and perceived quality of care of patients and their attendants in a specialized mental hospital in Bangladesh - Nuri, Nazmun Nahar; Sarker, Malabika; Ahmed, Helal Uddin; Hossain, Mohammad Didar; Beiersmann, Claudia; Jahn, Albrecht (BMC, 2022)
This article was published in the BMJ [© The Author(s) 2019. This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) and the definite version is available at: https://doi.org/10.1186/s13033-019-0303-x The Journal's website is at: https://ijmhs.biomedcentral.com/articles/10.1186/s13033-019-0303-x#citeas